Perceptions of Older Adults Regarding a Balanced diet for Maintaining Physical Health - Ramli Ramli; Juraidin Juraidin; Hairunnisah Hairunnisah (Universitas Muhammadiyah Palembang, 2026)
Rising life expectancy has given rise to the ageing population phenomenon, which contributes to declining physiological function and the emergence of degenerative diseases among older adults. A balanced diet serves as a key foundation for helping the elderly maintain independent daily activity, yet adherence to nutritional guidelines among this group remains low due to misconceptions about nutritional needs in old age. This study aims to explore how elderly individuals in Kalajena Village perceive the implementation of a balanced diet and to identify the physiological, social, and economic factors that hinder its practice. A descriptive qualitative approach was employed, involving six older adults as key participants and two supporting informants selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation, then processed through data reduction, categorization, and interpretation. The findings reveal that participants' understanding of balanced nutrition remains at a basic level and has not been fully translated into daily practice, with hypertension emerging as the most prevalent health condition. This gap stems from deeply rooted eating habits, limited family support for those living alone, and economic constraints restricting access to vegetables and fruit. The study concludes that perception, physiological condition, social support, and economic capacity are interrelated in shaping elderly eating behavior toward healthy ageing. Keywords: elderly perception; balanced diet; physical health; nutritional barriers; healthy ageing